Sistem Pakar Diagnosa Penyakit Gouty Arthritis dengan Menggunakan Metoda Forward Chaining - Hezy Kurnia (Jurnal KomtekInfo, 2019)
Gouty arthritis or gout is a type of joint disease that occurs due to uric acid levels that are too high in the blood. Under normal conditions, uric acid dissolves in the blood and passes through the urine. But under certain conditions, the body can produce uric acid in excessive amounts or experience a disruption in removing excess uric acid, so that uric acid accumulates in the body. Following this, a system is created that is able to provide patients with information like Gout by using methods forward chaining. This system is built using research and development methods that point to output in the form of expert system applications with the reading of the data carried out in forward chaining.